Prognostic Value of the Goutallier Scale for Paravertebral Muscle Atrophy in Predicting Disability and Pain Outcomes in Degenerative Lumbar Spinal Stenosis: A Longitudinal Cohort Study of 100 Patients - Giuseppe Corazzelli; Sergio Corvino; Chiara Di Domenico; Federico Russo; Vincenzo Meglio; Settimio Leonetti; Valentina Pizzuti; Marco Santilli; Alessandro D’Elia; Francesco Ricciardi; Sergio Paolini; Raffaele de Falco; et al. (Brain Sciences, 2025)
Background/Objectives: Degenerative lumbar spinal stenosis (LSS) is a prevalent cause of disability in elderly populations, often treated with decompressive surgery. However, postoperative functional outcomes are variable and influenced by factors beyond neural compression alone. This study aimed to investigate the prognostic significance of the Goutallier Classification System (GS), a radiological index of paravertebral muscle fatty degeneration, in predicting long-term postoperative disability and pain in elderly patients undergoing decompression for LSS. Methods: A retrospective cohort study was conducted on 100 elderly patients who underwent primary lumbar decompression surgery for LSS between January 2020 and July 2022, with a minimum two-year follow-up. Patients were stratified according to their preoperative GS grades assessed via MRI. The Oswestry Disability Index (ODI) and Visual Analog Scale (VAS) for pain were collected preoperatively and at follow-up. Changes in the ODI and VAS (ΔODI and ΔVAS) were analyzed to evaluate associations between GS grades and functional outcomes. Results: Significant improvements in the ODI (from 41.0 ± 17.5 to 16.9 ± 8.2) and VAS (from 6.23 ± 2.52 to 3.75 ± 2.38) were observed postoperatively (p < 0.01). However, higher GS grades were associated with greater residual disability and pain at follow-up, as well as with smaller postoperative improvements in these scores (p < 0.01 for ODI; p = 0.01 for VAS). Gender differences were noted, with females predominating in higher GS grades. No significant differences in comorbidities or complication rates were identified across GS subgroups. Conclusions: Preoperative paravertebral muscle degeneration, as measured by the GS, emerged as a significant predictor of postoperative disability and pain in elderly LSS patients. Incorporating GS assessment into preoperative planning may refine surgical risk stratification and inform shared decision-making to optimize long-term functional recovery.